Verification of patient position for proton therapy using portal X-Rays and digitally reconstructed radiographs - Van der Bijl, Leendert (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Applied Mathematics))--University of Stellenbosch, 2006.